The influence media in learning: the effect of videos and posters on learning concentration on the kihon ability of karate extracurricular students - Alfaritsi, Jumis Akbar; Bafirman, Bafirman; Alnedral, Alnedral; Putra, Aldo Naza (Jurnal Konseling dan Pendidikan, 2023)
Fundamental karate movement techniques (Kihon) are taught to students. Karate's fundamental techniques consist of blocks, strikes, jabs, and kicks. Karate novices are required to master kihon, or fundamental techniques, from which further training is derived. The effect of rigid and repetitive training methods on students is one of boredom and saturation. A method employed to enhance students' proficiency in kihon is the utilization of visual media. The objective of this study is to compare the impact of video media and poster image learning in high-concentration and low-concentration groups on the Kihon ability of SMPN 23 Pekanbaru extracurricular karate students.The experimental methodology utilized in this investigation is a 2x2 factorial experimental design. The study's population comprises 60 pupils enrolled in extracurricular karate at SMPN 23 Pekanbaru. The sample consisted of 16 students, which were divided into two groups. The data were analyzed utilizing two-way ANOVA and the T-test. Conclusions of the investigation The impact of video media and poster images in the classroom on the kihon abilities of students varies, irrespective of their placement in the high-concentration or low-concentration group under instruction. Students' kihon abilities are not influenced by the utilization of video media and poster images to acquire knowledge, irrespective of their placement in the high-concentration or low-concentration group.The mean difference in learning outcomes between video media and poster images was notably greater in both the high-concentration and low-concentration groups when compared to learning via poster images.